STRATEGI PENINGKATAN PEMASARAN TERHADAP JARINGAN INTERNET NIRKABEL (WIFI) PT. DEACOM TEKNOLOGI DI DESA SIPODECENG - Suardi, Muh Irfan (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
Marketing strategy is one of the basics used in developing overall company planning, Wi-Fi has gained enormous public acceptance. The problem formulation in the strategy for improving wireless internet network (WIFI) marketing is maintaining good relationships with existing customers, increasing sales promotions, and customer relationship management systems help businesses understand customer needs, track interactions, and provide more personalized and responsive service. The aim of this research is to find and analyze the strategies used by PT. Deacom Technology in Sipodeceng Village to increase marketing of wireless internet networks (WiFi). In the current digital era, getting fast and stable internet access is very important, especially in rural areas where infrastructure is limited. The sample for this research was 57, the methods used in this research included observation, communication, and use of WiFi services. The research results show that PT. Deacom Technology must improve several marketing strategies, such as improving services, creating more efficient promotional programs, and increasing price adjustments. Therefore, PT. Deacom Technology to improve marketing of wireless internet networks (WIFI) in Sipodeceng Village is considered "good". The use of mobile devices such as smartphones, tablets and laptops has recently increased, increasing the demand for fast and reliable internet connections everywhere. As a result, many fields such as tourism, education, business, and industry are experiencing an increase in demand for fast and reliable Wi-Fi services. A communication strategy is a plan made consciously to overcome the difficulties a person faces in achieving communication goals. Stations sharing one radio frequency communication channel are a combination of computer and interface controller.